Balón intragástrico colocado por vía endoscópica para manejo de la obesidad - Braghetto M., Italo; Rodríguez N., Alberto; Csendes J., Attila; Papapietro V., Karin; Díaz G., Ema; Brunet L., Luis; Ocksenberg R., Danny; Valladares H. , Héctor; Reyes O., Diego; Riffo C., Paola (Revista Hospital Clínico Universidad de Chile, 2005)
Resumen no disponible